Applying the Brand Identity Prism to the Development of a Sustainable Coffee Edutourism Destination in Sumbertangkil Village, Malang, Indonesia - Aditya Dwi Putra Bhakti Bhakti; Moch. Fuad Nasvian (FAKULTAS DAKWAH UIN SALATIGA, 2025)
Sustainable tourism has become a global priority due to its significant economic impact. In Indonesia, coffee one of the country’s leading agricultural commodities holds considerable potential for development through locally based edutourism initiatives. This study aims to identify the brand identity dimensions of coffee-themed edutourism in Sumbertangkil Village, Malang, using Jean-Noël Kapferer’s Brand Identity Prism (BIP) framework. An exploratory qualitative methodology was applied, involving focus group discussions with Pokdarwis administrators and local community members in Sumbertangkil. The findings reveal that the brand identity of this coffee destination is shaped by the synergy among the dimensions of personality, relationship, and self-image, supported by attributes such as warmth, participatory engagement, and educational experiences. A key challenge identified is the lack of consistency in visual identity elements, such as logos and a cohesive branding system for the destination. This study highlights the importance of community involvement and the integration of sustainability values as essential foundations for differentiation and for strengthening the brand of this coffee edutourism destination.